Optimization of laminated composite plates for maximum biaxial buckling load - Pham, Dinh Nguyen (H. : ĐHQGHN, 2020)
This paper proposes an optimization procedure for maximization of the biaxial buckling load of laminated composite plates using the gradient-based interior-point optimization algorithm. The fiber orientation angle and the thickness of each lamina are considered as continuous design variables of the problem. The effect of the number of layers, fiber orientation angles, thickness and length to thickness ratios on the buckling load of the laminated composite plates under biaxial compression is investigated. The effectiveness of the optimization procedure in this study is compared with previous works.